2017
DOI: 10.1155/2017/5812650
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Stigma in Nigeria: Review of Research Studies, Policies, and Programmes

Abstract: Nigeria has about 3.8 million people living with HIV, the second largest globally. Stigma and discrimination are major barriers to testing, treatment uptake, and adherence. In this review, we synthesized information on research studies, policies, and programmes related to HIV-stigma in Nigeria. This was with a view to identify critical areas that research and programmes must address in order to accelerate the progress towards zero (new infections, discrimination, and death) target by year 2030. Existing studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…On the other hand, the lower mean score in the social relationship domain could be attributed to persisting pockets of social stigma and discrimination, including self-stigmatization, which is a predominant feature among PLWHA. Stigma and discrimination have been shown to be major barriers to treatment uptake and adherence, and can significantly reduce patient's QOL [28]. In a Northern Ethiopian study, high perceived stigma was strongly associated with poor psychological quality of life [29].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the lower mean score in the social relationship domain could be attributed to persisting pockets of social stigma and discrimination, including self-stigmatization, which is a predominant feature among PLWHA. Stigma and discrimination have been shown to be major barriers to treatment uptake and adherence, and can significantly reduce patient's QOL [28]. In a Northern Ethiopian study, high perceived stigma was strongly associated with poor psychological quality of life [29].…”
Section: Discussionmentioning
confidence: 99%
“…The problem of harmful cultural practices is a psychosocial issue that promotes HIV-related stigma, especially among women, which increases vulnerability to HIV infection (Anugwom and Anugwom, 2016;Odimegwu, Akinyemi, & Alabi, 2017;Stockton, Giger, & Nyblade, 2018). Also, it was indicated that HIV stigma leads to discrimination and stigmatization of PLWHA by members of the society (Famoroti, Fernandes, & Chima, 2013;Srithanaviboonchai, Chariyalertsak, Nontarak, Taneepanichskul, & Aekplakorn, 2017).…”
Section: R E S E a R C H H I G H L I G H T Smentioning
confidence: 99%
“…Culture, therefore, defines HIV as a women problem (Girum et al, 2018). Odimegwu et al (2017) indicated that there is a high rate of HIV infection among women in Nigeria. Reasons for the HIV prevalence is based on the harmful cultural practices, including female genital mutilation (Klein, Helzner, Shayowitz, Kohlhoff, & Smith-norowitz, 2018;Koski & Heymann, 2017), postpartum sexual abstinence during breastfeeding (Dev et al, 2019;Shabangu & Madiba, 2019), sexual intercourse during menstruation (Di Guardo et al, 2019;Laganà et al, 2017), gender inequality (Jayachandran, 2014), and tribal marks and scarification (Breuner, Levine, & AAP The Committee on Adolescence, 2017).…”
Section: R E S E a R C H H I G H L I G H T Smentioning
confidence: 99%
“…According to the Nigerian HIV and AIDS Indicator and Impact Survey (NAIIS) report 2018, the current national prevalence of HIV is estimated at 1.4% (15-49 years), with an estimated 1.9 million PLWHA in Nigeria. This report borders across age and indicates 12% of PLWHA are between the ages of 0-14 years while 75% are between 15-49 years and 13% are 50 years and above in Nigeria [16,17]. Adolescents (10-19 years) account for 8% of persons living with HIV.…”
Section: Introductionmentioning
confidence: 99%